Early life history of an estuarine grapsid crab, Helice leachi Hess - Mia, MD Younus; Shokita, Shigemitsu (Indian Journal of Fisheries, 2011)
Early life history of Helice leachi was studied in the laboratory conditions throughobserving the larval metamorphosis and salinity optimization for the larvae.Larval development consists of 5 zoeal and 1 megalopal stages before theymoulted to the first crab stage. Eighty percent survival rate of zoea I-V andmegalopa at water salinity of 20 and 15 ppt, respectively, suggest that larvae ofH. leachi pass their early life within the mangrove area.